DAYA SAING EKSPOR MINYAK KELAPA SAWIT INDONESIA - Ratnawati Nurkhoiry (Pusat Penelitian Kelapa Sawit, 2017)
Indonesia is the biggest palm oil exporter, however how much Indonesia's competitiveness compared to other exporting countries still need to study. This study measures competitiveness using 10 indicators of trade from the World Bank divided into 3 major groups, namely; export share, market penetration and comparative advantage. Using trade data from UN Comtrade of palm oil in HS code, 2004-2016. Referring to the results of 10 indicators, Indonesia; share exports are increasing, stronger market penetration, more diversified exports, and increased comparative advantage. Malaysia as exporter, although the share of exports is declining but still has strong market penetration, diversified exports and comparative advantage.